Frequent isolation of Francisella tularensis from Dermacentor reticulatus ticks in an enzootic focus of tularaemia - Hubálek, Z; Treml, F; Halouzka, J; Juricová, Z; Hunady, M; Janík, V (Medical and veterinary entomology, 1996)
A total of 924 questing Dermacentor reticulatus (Fabricius), 504 Ixodes ricinus (L.), sixty Haemaphysalis concinna Koch and 718 mosquitoes (Aedes spp.) were examined in a floodplain forest ecosystem during the 1994-95 outbreak of tularaemia in South Moravia, Czech Republic. Francisella tularensis was not isolated from H.concinna ticks or Aedes spp. mosquitoes, whereas twenty-one isolates were recovered from the other haematophagous arthropods. Dermacentor reticulatus revealed a significantly higher infection rate (2.6%) than I.ricinus (0.2%). This tick species acts as principal vector for tularaemia in the enzootic focus. Monitoring of D.reticulatus for F.tularensis thus seems to be a very efficient approach in the surveillance of tularaemia in the flood-plain forest ecosystems of Europe.
Keywords: Ticks; ekosystém; Ixodes; Česká republika; Dermacentor; Arthropod Vectors; tularemie; Aedes; Czech Republic; členovci - vektory; zvířata; Humans; králíci; klíšťata; Rabbits; klíště; Tularemia; Francisella; Ecosystem; lidé; Animals